2021
DOI: 10.1002/1873-3468.14180
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐scale metabolic modelling of SARS‐CoV‐2 in cancer cells reveals an increased shift to glycolytic energy production

Abstract: Cancer is considered a high‐risk condition for severe illness resulting from COVID‐19. The interaction between severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) and human metabolism is key to elucidating the risk posed by COVID‐19 for cancer patients and identifying effective treatments, yet it is largely uncharacterised on a mechanistic level. We present a genome‐scale map of short‐term metabolic alterations triggered by SARS‐CoV‐2 infection of cancer cells. Through transcriptomic‐ and proteomic‐in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 125 publications
(141 reference statements)
1
15
0
Order By: Relevance
“…Experiments performed in human primary hepatocytes further evidenced a modulation of intracellular glucose and extracellular lactate upon infection. These data are consistent with previous work showing that viral infection promotes glycolysis 62 . Remarkably, in our fluxomics results performed with the primary hepatocytes, infection resulted in an increase of fumarate and malate.…”
Section: Discussionsupporting
confidence: 94%
“…Experiments performed in human primary hepatocytes further evidenced a modulation of intracellular glucose and extracellular lactate upon infection. These data are consistent with previous work showing that viral infection promotes glycolysis 62 . Remarkably, in our fluxomics results performed with the primary hepatocytes, infection resulted in an increase of fumarate and malate.…”
Section: Discussionsupporting
confidence: 94%
“…However, because this model only incorporated a SARS-CoV-2 virus biomass target function (VBOF) into a GEM of human alveolar macrophages, its predictive power could be further improved by fitting metabolic constraints to the diseased state of a metabolic network. A similar approach of modelling the infection in the hepatocyte-derived cellular carcinoma cell line Huh7 using the manual extension of the Recon 2.2 model was reported by Yaneske et al [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Application of GSMM by integrating the host transcriptomics and metabolomics and the virus biomass function can provide information about the altered metabolic reactions. Earlier seminal studies in the context of SARS-CoV-2, based on host-virus GSMM of human alveolar macrophages (Renz et al, 2020), human airway epithelial cells (Bannerman et al, 2021), and liver cancer cells (Huh7) (Yaneske et al, 2021), reported that the role of biosynthesis and degradation of amino acids, glycolytic shift, and energy metabolism are essential for progressive viral replication. As the SARS-CoV-2 was not detected in the blood cell populations in our cohort, we therefore hypothesized that the systemic metabolic alterations are most likely because of the bystander effect of the infection due to the inflammatory conditions.…”
Section: Articlementioning
confidence: 99%